2020
DOI: 10.1055/a-1217-2397
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-2019 (COVID-19): An Updated Review

Abstract: The current outbreak of novel Coronavirus Disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major pandemic situation and a catastrophe for humans. COVID-19 is a severe infectious disease particularly of the respiratory system characterized by fatal complications such as severe acute respiratory distress syndrome (SARS), pneumonia, cardiac arrhythmia, kidney failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
0
31
0
3
Order By: Relevance
“…This finding should be treated with caution-it needs to be validated in independent studies and expression of these pathways may not translate to an increase in cancer incidence. However, COVID-19 follows a more chronic course and with more widespread systemic manifestations than other acute respiratory viral infections [3]; and there are longer-term consequences of this infection that are only just beginning to be described [29]. Any predisposition to malignancy could take many years to become apparent; it is a vital area for future research given the scale of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding should be treated with caution-it needs to be validated in independent studies and expression of these pathways may not translate to an increase in cancer incidence. However, COVID-19 follows a more chronic course and with more widespread systemic manifestations than other acute respiratory viral infections [3]; and there are longer-term consequences of this infection that are only just beginning to be described [29]. Any predisposition to malignancy could take many years to become apparent; it is a vital area for future research given the scale of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…manifestations with other respiratory viral infections such the common cold (rhinoviruses and common human coronaviruses) and influenza, it has a number of differences including prolonged viral shedding that may last many weeks, progression to more severe disease in a proportion of patients in the second week of illness, and extrapulmonary manifestations including cardiovascular and thromboembolic disease [3,4]. The disease differs in frequency and severity between ethnic groups and although these differences are most likely driven by socioeconomic factors, it has been suggested that biological factors may also contribute [5,6].…”
mentioning
confidence: 99%
“…Multiple organ failure is the most common cause of death in these patients. 25,26 It is crucial to develop effective treatment regimens for COVID-19 patients with multiple comorbidities, as patients' past medical history is an essential contributor to possible organ injuries in these patients. Further observations will be required to comprehensively understand the full spectrum of COVID-19 clinical features in patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…CO-VID-19 hastalığının erken döneminde lenfosit sayısı azalmış olarak saptanırken lökosit sayısı normal ya da düşük çıkabilir. [10] Pandemi döneminde hasta seçiminde yapılacak operasyonun endikasyonu kadar COVID-19 hastalığı şüphesinin olup olmaması da hasta, klinik ve cerrahi ekip açısından oldukça önemlidir. [11,12] Özellikle trakea ve akciğer cerrahisi planlanan hastalarda bu ihtimali göz önünde bulundurmak gerekmektedir.…”
Section: Hasta Seçimiunclassified